Strategi Badan Narkotika Nasional (BNN) Dalam Mencegah Peredaran Narkotika di Kota Makassar - Nurlaelah, Nurlaelah; Harakan, Ahmad; Mone, Ansyari (Universitas Gorontalo, 2019)
The strategy in preventing the circulation of narcotics is one of the forms of performance carried out by the National Narcotics Agency and in collaboration with various agencies from government agencies, non-governmental organizations as well as the public in preventing drug trafficking in the city of Makassar which has experienced very high rates of drug trafficking. high. resulting in a large number of drug users mainly in the community. This type of research is qualitative. Data is collected through observation and documentation and interviews with informants. The results of this study indicate that the National Narcotics Agency's strategy in preventing the circulation of narcotics in the city of Makassar, from several strategic indicators namely Suplay Reduction, Demand Reduction and Harm Reduction has been carried out in accordance with the P4GN. The supporting factor in the National Narcotics Agency's strategy in preventing the circulation of narcotics is Presidential Instruction No. 12 of 2011 and support and cooperation from various agencies. While the inhibiting factor is the availability of human resources, budget and supporting tools. Strategi dalam mencegah peredaran narkotika merupakan salah satu bentuk kinerja yang dilakukan oleh Badan Narkotika Nasional dan bekerja sama dengan berbagai instansi baik dari instansi pemerintah, non pemerintah dan juga kalangan masyarakat dalam mencegah peredaran narkotika di kota Makassar yang selama ini mengalami tingkat laju peredaran narkotika yang sangat tinggi. sehingga mengakibatkan banyaknya pengguna narkotika utamanya pada kalangan. Jenis penelitian ini adalah kualitatif. Data dikumpulkan melalui observasi dan dokumentasi serta wawancara terhadap informan. Hasil penelitian ini menunjukkan bahwa Strategi badan Narkotika Nasional dalam mencegah peredaran narkotika di kota makassar, dari beberapa indikator strategi yaitu Suplay Reductiont, Demand Reduction dan Harm Reduction sudah dilaksanakan sesuai dengan P4GN. Faktor pendukung dalam Strategi Badan Narkotika Nasional dalam mencegah peredaran narkotika adalah Instruksi Presiden No. 12 tahun 2011 serta dukungan dan kerja sama dari berbagai instansi. Sedangkan faktor penghambatnya adalah ketersediaan sumber daya manusia, anggaran dan alat pendukung.